Arsenic natural and anthropogenic - Matschullat, Jörg; Deschamps, Eleonora (CRC Press, 2011)
"Arsenic in the environment has been studied in many, mostly unrelated works dealing with very specific individual aspects. This book provides an interdisciplinary and comprehensive examination into Arsenic's behaviour in air, water, soils and sediments, plants and the human body. Based on state-of-the-art investigations into the global arsenic cycle, the related human toxicology and available remediation technologies, it assesses arsenic in all the environmental compartments. Using the results of primary research, the authors offer concrete suggestions for risk reduction and management of environmental pollution that allow the reader to successfully tackle similar problems and find sustainable solutions.The book consists of three parts: 1. review of the current knowledge of Arsenic behaviour in the environment (global biogeochemical cycles), toxicology, remediation techniques, immobilization technologies and environmental legislation; 2. Case studies for mining-related arsenic problems; 3. Discussion of mitigation and remediation technologies and approaches such as environmental education, hygiene training, backed by real experience and successful implementation in the region"-- Provided by publisher.
"A Balkema book."
Keywords: Arsenic -- Environmental aspects.; elektronické knihy; electronic books